Performance of Village Health Volunteers in Song District, Phrae Province - Komnanton , Tichaporn; Bodeerat, Chot (Journal of Modern Learning Development, 2021)
The objectives of this research were 1) the performance of village health volunteers in Song District, Phrae Province, 2) to compare personal factors with the performance of village health volunteers in Song District, Phrae Province and 3. ) Practice Guidelines for Village Health Volunteers In the two districts, Phrae Province, this research was a combination of methods. Between quantitative research and qualitative research The research instruments were questionnaires and interviews. The sample used for the research was 318 village health volunteers (Or Sor.Sor.) In Song District, Phrae Province, obtained by substituting values ​​in Taro Yamane’s formula and 12 key informants in a small group. The statistics used frequency, percentage, mean, standard deviation, t-test and F-test with One Way ANOVA. Results of the Research 1) Overall, the performance of the village health volunteers in Song District, Phrae Province was at the high level. 2) The comparison found that the village health volunteers having the different gender, age, degree of education, occupation, income, and period of being the village health volunteer had no the different performance of the village health volunteers in Song District, Phrae Province. 3) The guidelines for the performance of the village health volunteers in Song District, Phrae Province were: the village health volunteers should perform the principles of the family health volunteers and the role of the village health volunteers with the disease surveillance, prevention and controlling in the area, promote and solve the health problem with the application of the local wisdom, the herbs and using the hashish in the medicine, the telemedicine, the health application and the participative leader for the health promotion.